Evaluate the Effectiveness of Agaricus bisporus (Spawn) on Control Damping – off Caused by Pythium aphanidermatum on Cucumber (Baghdad Science Journal, 2016)
This study was conducted to test the effectiveness of Agaricus bisporus inoculums (spawn) in the ratio of (0.25, 0.5 and 1%) v/v to control Pythium aphanidermatum fungus the causal agent of damping- off disease of cucumber plant. results showed the ability of A. bisporus fungus to protect the seedlings from incidence by P. aphanidermatum . all treatments of edible fungus inoculums were significantly different from pathogen treatment after 15 day of planting and there was no significant difference found from control treatment (without pathogen) . the successful of A. bisporus was continued to protect the seedlings after 30 and 45 day after planting. The numbers of seedlings were (8, 7.25 & 7.25) respectively compared to 5.5 seedlings in control treatment (with pathogen) on the 45th. Disease severity was reached (4.5) and the disease index was (90%) in pathogen treatment that significantly different from all other treatments. At the same time the treatments of the tested ratio (0.25, 0.5, 1) % were able to reduce the ratio of disease severity and disease index by 22% compared to control treatment (with pathogen). The results showed that all treatments of edible fungus inoculums that used to control P. aphanidermatum were achieved significant increase in growth index represented by plants height which reached to (30, 31, 30.3) cm respectively, compared to control treatment (with pathogen) ( 22.3)cm. The results reflected on plants wet weight (16.92, 18.85, 16.92)g were significant increase from control treatment (with pathogen) ( 12.61)g. As well as the significant increase in plants dry weight of edible fungus inoculums were reached (1.75, 2.04, 2.16) g compared to control treatment (with pathogen) (1.2)g.